BUMDES MANDIRI, DESA SEJAHTERA: OPTIMALISASI PENGELOLAAN BUMDES UNTUK EKONOMI LOKAL DESA PANGI KABUPATEN TOLITOLI - Syahrina marsyah; Annisa Nurfitriani; Aprianti Aprianti; Rahma Rahma; Susi Febriani Valentin; Moh Ahksan Ishak Ambotje; Mardiana Mardiana (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Management of Village-Owned Enterprises (BUMDes) to support the economic welfare of village communities. The activity was carried out in Pangi Village, Baolan District, Tolitoli Regency. The main activities carried out included training, technical assistance, and evaluation focused on financial management, marketing strategy planning, business variety development, and increasing operational efficiency. The results of the activity showed an increase in the capabilities of BUMDes managers, especially in creating accountable financial reports, developing digital-based marketing strategies, and identifying new business opportunities. In addition, the average income of BUMDes increased by 30%, and community involvement in BUMDes activities also increased. However, several challenges, such as limited access to technology and resistance to change, still need to be addressed through follow-up programs so that the results achieved can be sustained. Overall, this program has made a positive contribution to increasing the professionalism of BUMDes management and strengthening the village economy.